Mucoadhesive Nanostructured polyelectrolyte complexes as potential carrier to improve zidovudine permeability - Pedreiro, Liliane Neves [UNESP]; Cury, Beatriz Stringhetti Ferreira [UNESP]; Gremião, Maria Palmira Daflon [UNESP] (American Scientific Publishers, 2016)
Mucoadhesive drug delivery systems have been widely investigated as a strategic to allow the raising of intestinal residence time of drugs and the intimate contact with the intestinal mucosa, both factors that increase the local concentration gradient. Zidovudine (AZT) mucoadhesive nanostructured polyelectrolyte complexes were obtained by chitosan (CS)-hypromellose phthalate (HP) interactions in order to favor the permeability through biologicalmembranes and the AZT absorption. Particle size and morphology analyses showed the obtaining of nanoparticulate delivery systems, with AZT loaded about of 65%. The characterization by DSC, X-ray diffraction and FTIR showed a new crystalline structure formed in which the drug remained molecularly dispersed, without changing this structure. The reduced release rates in the simulated gastric medium and the control of release rates in simulated intestinal medium of AZT were demonstrated by in vitro release studies. The nanoparticles liquid uptake ability associated to the mucoadhesiveness by electronic interaction between the particles and mucus revealed that the drug delivery system developed in this work is a promising approach to improve the permeation of this drug throughout the intestinal mucosa.
Keywords: Mucoadhesion; Permeability; Polyelectrolyte complexes; Polymeric nanoparticle; Zidovudine